2021
DOI: 10.1007/s10608-020-10202-4
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Emotion Regulation in College Athletes: A Preliminary Exploration of Daily Savoring, Acceptance, and Cognitive Reappraisal

Abstract: Background Despite increasing interest in positive psychological states, we know little about how regulatory responses to positive (savoring) compared to negative events (e.g. acceptance, cognitive reappraisal) influence emotional functioning. Savoring may be particularly helpful for athletes who are often trained to attend more to negative (e.g. rectifying weaknesses) compared to positive stimuli (e.g. enjoying progress). Methods Sixty-seven college athletes completed a two-week daily diary study. Using multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 98 publications
1
13
1
Order By: Relevance
“…These results mean that passionate athletes with a harmonious relationship with sport are most likely to respond to good times by attempting to enhance or prolong their positive feelings, and that doing so may protect them from becoming emotionally or physical exhausted, feeling a reduced sense of accomplishment, and developing negative attitudes toward their sport. Savoring thus appears to be an adaptive way of responding to positive experiences in sport, a finding that is in line with recent findings with athletes (Doorley & Kashdan, 2021) and with research conducted in nonathlete populations (e.g., Wilson et al, 2020). Research on savoring in sport is just beginning, and more research in this area is needed to help learn more about the antecedents and outcomes of savoring for all types of sport participants.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These results mean that passionate athletes with a harmonious relationship with sport are most likely to respond to good times by attempting to enhance or prolong their positive feelings, and that doing so may protect them from becoming emotionally or physical exhausted, feeling a reduced sense of accomplishment, and developing negative attitudes toward their sport. Savoring thus appears to be an adaptive way of responding to positive experiences in sport, a finding that is in line with recent findings with athletes (Doorley & Kashdan, 2021) and with research conducted in nonathlete populations (e.g., Wilson et al, 2020). Research on savoring in sport is just beginning, and more research in this area is needed to help learn more about the antecedents and outcomes of savoring for all types of sport participants.…”
Section: Discussionsupporting
confidence: 82%
“…Research outside of sport has shown that savoring is an adaptive response to positive experiences that predicts various positive outcomes including greater happiness and overall wellbeing, and fewer symptoms of depression and negative feelings (e.g., Hurley & Kwon, 2012Wilson et al, 2020). Research is now starting to emerge that shows that athletes can also benefit from savoring positive experiences (Doorley & Kashdan, 2021). The current research increased our understanding of savoring in sport in at least two ways.…”
Section: Savoring Sportmentioning
confidence: 75%
See 2 more Smart Citations
“…Based on previous statements, gender differences in emotion regulation and emotional reactivity requires further explanation. On the other hand, several studies confirmed that athletes have higher dispositional hope ( Curry et al, 1997 ), optimism ( Nicholls et al, 2008 ), perseverance ( Laborde et al, 2014 , 2016 ), resilience ( Padesky and Mooney, 2012 ), and adaptive emotion regulation strategies ( Lane et al, 2009 , 2011 ; Laborde et al, 2014 ; Doorley and Kashdan, 2021 ). Furthermore, it has been reported that professional athletes had better mental health status than non-athletes ( Şenışık et al, 2021 ) and showed lower negative emotional state values than expected average ( Leguizamo et al, 2021 ) during COVID-19 lockdown.…”
Section: Introductionmentioning
confidence: 99%